PERAN ULAMA DALAM KOMUNIKASI POLITIK LOKAL: STUDI STRATEGI DAN PENGARUH PADA PEMILIHAN KEPALA DAERAH - Nurul Azizah; Mohammad Armoyu (Fakultas Dakwah Universitas Ibrahimy, 2025)
Moral support and political communication in the local area have a huge influence on the victory of Regional Head candidates in Tapal Kuda. This research aims to analyze the role of ulama in local political communication, the strategies used, and their impact on the results of regional head elections. This research uses a qualitative approach with a case study method in two areas that have a strong religious culture, namely Probolinggo, Bondowoso, Jember and Situbondo Regencies. The results found were Moral Endorsement, namely ulama providing explicit support for certain candidates, often by linking the candidate's character to religious values. Dissemination of Political Messages through religious lectures, mass mobilization, ulama mobilize their support base to attend campaigns and use religious networks to strengthen political support.